2020
DOI: 10.1177/1071100720904033
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Lesser Metatarsophalangeal Joint Interpositional Arthroplasty With Tendon Allograft

Abstract: Background: Lesser toe metatarsal head degeneration and collapse can cause significant pain and disability. In the setting of global metatarsal head collapse, there are limited operative options. The purpose of our study was to evaluate clinical and radiographic outcomes after lesser toe metatarsophalangeal (MTP) joint interpositional arthroplasty with a tendon allograft and to describe the operative technique. Methods: We retrospectively reviewed a consecutive series of patients treated by 3 fellowship-traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. [39][40][41][42][43][44] Çevik et al 44 reported the mid-to long-term results of interposition arthroplasty with the extensor digitorum brevis tendon. After a mean follow-up 133.8 (range, 60-198) months, the AOFAS scores improved as did the range of motion in dorsiflexion and plantar flexion.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Several articles have reported good clinical outcomes of interposition arthroplasty using soft tissue such as the extensor digitorum longus, extensor digitorum brevis, palmaris longus, periosteum with a fat pedicle graft, and allograft of the semitendinosus tendon. [39][40][41][42][43][44] Çevik et al 44 reported the mid-to long-term results of interposition arthroplasty with the extensor digitorum brevis tendon. After a mean follow-up 133.8 (range, 60-198) months, the AOFAS scores improved as did the range of motion in dorsiflexion and plantar flexion.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
“…The AOFAS and VAS scores also improved. Stautberg et al 43 reported the clinical and radiographic outcomes of interposition arthroplasty with improvements in the VAS score. The Foot and Ankle Ability Measure sports subscale score also significantly increased, and 90% of patients reported their function as normal or nearly normal after surgery.…”
Section: Joint-sacrificing Procedures Interposition Arthroplastiesmentioning
confidence: 99%
See 1 more Smart Citation